Anterior Segment Biometry with Phenylephrine and Tropicamide during Accommodation Imaged with Ultralong Scan Depth Optical Coherence Tomography. (25th February 2019) - Zhang, Junna; Ni, Yang; Li, Peng; Sun, Wen; Liu, Mengyun; Guo, Dongyu; Du, Chixin
Abstract : Purpose . To investigate the influence of phenylephrine and tropicamide on anterior segment biometry with ultralong scan depth optical coherence tomography (UL-OCT) during accommodation. Methods . In this study, 20 left eyes of healthy volunteers with a mean ± standard deviation age of 31.05 ± 5.84 years and a mean refraction of −1.16 ± 1.11 diopters (range 0∼−3.0 D) were imaged using UL-OCT after instillation of artificial tears, phenylephrine, and tropicamide in three follow-up trials, respectively. At each follow-up trial, two repeated measurements were performed at states of relax and 5D accommodative stimulation. The dimensional parameters included central corneal thickness (CCT), anterior chamber depth (ACD), pupil diameter (PD), lens thickness (LT), and horizontal radii of the lens anterior and posterior surface curvatures (LAC and LPC). Results . Tropicamide led to larger pupil, deeper ACD, thinner LT, and flatter crystalline lens surface (P < 0.05 ). Phenylephrine induced an increase in PD (P < 0.05 ), while no significant changes were seen in ACD, LT, LAC, and LPC (P > 0.05 ). CCT did not change after both phenylephrine and tropicamide instillation in this study (P > 0.05 ). Tropicamide induced the loss of accommodation and phenylephrine achieved pupil dilation without affecting the accommodation. PD, ACD decreased, LT increased significantly and the anterior and posterior surface of the lens in a 6.294 mm of diameter optical zone became steeper during accommodation after administration of phenylephrine (P < 0.05 ). Conclusion . The anterior segment physiology changed after tropicamide instillation. Besides, tropicamide induced the loss of accommodation and phenylephrine preserved the accommodation with a larger pupil. And, the anterior and posterior surface of lens in a 6.294 mm of diameter optical zone became steeper during the accommodation.